Subspace Tracking, Discrimination of Unexploded Ordinances (UXO) in Airborne Magnetic Field Gradients - Jeoffreys, Mark (My University, 2007)
Statistical and algebraic techniques of subspace tracking were tested for filtering the earth’s response from airborne magnetic field gradients in order to discriminate the relatively small response (dipole) of objects on the earth’s surface, such as UXO. Filtering the data was not very effective with these methods but a subspace was found in the data for the magnitude of the magnetic moment of the dipole. This subspace is easily obtained using the singular value decomposition and can be used for an approximate location, without depth estimation, as well as the relative size of the dipole.
Student Number : 9807515F - MSc Dissertation - School of Computational and Applied Mathematics - Faculty of Science
Keywords: subspace tracking; Principal Components; Magnetic Field Gradients; Unexploded Ordinances; UXO